ПРИРОДА И ИСТОЧНИКИ ВОЗНИКНОВЕНИЯ КОНФЛИКТОВ В ОБЩЕСТВЕ: ПРАВОВОЙ АСПЕКТ (Journal of actual problems of jurisprudence, 2019)
This article describes the nature, sources and causes of conflict in society. Description of the legal conflict as a form of social conflicts, that is,marked by features that characterize the conflict with the position of the law.